Trends in emergency department visits for acute intoxication: a 3-year retrospective study in Hangzhou, East China - Li, Chengle; Zhang, Hong; Yang, Bo (Frontiers in Public Health, 2025)
BackgroundEpidemiological studies on acute intoxication contribute to the development of emergency care, particularly in hospital settings. Understanding the demographics and risk factors of acute intoxication aids in designing targeted public health interventions and educational campaigns to reduce its incidence.ObjectiveThe objective of this research was to describe the epidemiological trends and patterns of acute intoxication cases, as well as the types of intoxication, at Tongde Hospital of Zhejiang Province, a general hospital located in eastern China.MethodsA retrospective review of medical records was conducted for all patients presented to the emergency department with acute intoxication at Tongde Hospital of Zhejiang Province between 2020 and 2022. The data collected from the hospital information system included gender, age, visit time, types of intoxication cases, length of hospital stay, treatment administered, and clinical outcomes. Univariate analysis was performed to identify factors associated with suicidal and non-suicidal patients.ResultsDuring the three-year period from 2020 to 2022, a total of 550 acute intoxication patients were admitted to the emergency department. Females constituted the majority of the cohort, representing 72.3% (n = 398) of the total cases, and the age group of 13 to 40 years made up the largest proportion at 74.7%. The number of cases increased annually, with poisoning incidents varying by month and week. The most common substances involved were drugs (79.6%), followed by alcohol mixed with drugs (5.8%), gases (6.2%), pesticides (3.8%), household chemical products (3.1%), and plants (1.4%). The monthly distribution of cases showed peaks in June, September, and April, while the weekly distribution peaked on Mondays and Thursdays. The mean time interval between toxin exposure and hospital admission was 5.40 ± 9.93 h. Statistical analysis revealed that gender, age, and the type of poisonous substance were all significant factors associated with suicide. After treatment, 80.5% (n = 443) of patients were discharged home within 24 h, while 19.5% (n = 107) required hospitalization.ConclusionThis study indicates an increasing proportion of suicidal cases among all poisoning incidents, particularly among young women. Drug intoxication was the most common cause, with antidepressants, antipsychotics, and benzodiazepines being the most commonly involved substances. These findings underscore the urgent need for mental health support, pharmaceutical safety measures, and preventive education targeting high-risk groups, particularly young women.